The rebirth of the current source inverter: advantages for aerospace motor design - Madonna, Vincenzo; Migliazza, Giovanni; Giangrande, Paolo; Lorenzani, Emilio; Buticchi, Giampaolo; Galea, Michael (Institute of Electrical and Electronics Engineers Inc., 2019)
It is well known and widely accepted that the voltage source inverter (VSI) now dominates the world of electrical drives. Its success is probably due to its simplicity, high efficiency, and the widespread availability of VSs. This popularity has, in turn, influenced the evolution of the semiconductor industry, which has focused in recent years on devices tailored for VSIs. Thus, products such as depletion devices (normally off) and those without reverse voltage blocking have been widely marketed and used.